PENGARUH PENGETAHUAN BUDAYA POP JEPANG TERHADAP MOTIVASI BELAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU - Ari Bramantyo Suryo Tamtomo; Nana Rahayu; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: In learning a foreign language, especially in this case is Japanese, every student must have an interest in learning so that they have a strong motivation in learning. Interest in this can be obtained starting from a person's interest in a culture, or even the language itself. At the university level, students who study Japanese have ways to learn Japanese pop culture itself, starting from self-study such as watching youtube videos, anime, just reading news or articles about the culture, and there are also students who study in class. The method of data collection is done by distributing tests and questionnaires that have been made, in the form of a collection of questions to obtain information that is considered representative with the aim of obtaining the information needed in this study. By using a sample of 50 people from 5 batches of Japanese Language Education FKIP Riau University. From the results of the study, it was found that knowledge of pop culture on student motivation has a strong correlation, it also has a positive and significant relationship where knowledge of pop culture on motivation of 50 students is 49.4%.Key Words: Pop culture, Learning motivation, Correlation